eTFC-01: a dual-labeled chelate-bridged tracer for SSTR2-positive tumors - Dylan Chapeau; Savanne Beekman; Maryana Handula; Erika Murce; Corrina de Ridder; Debra Stuurman; Yann Seimbille (SpringerOpen, 2024)
Abstract Background Integrating radioactive and optical imaging techniques can facilitate the prognosis and surgical guidance for cancer patients. Using a single dual-labeled tracer ensures consistency in both imaging modalities. However, developing such molecule is challenging due to the need to preserve the biochemical properties of the tracer while introducing bulky labeling moieties. In our study, we designed a trifunctional chelate that facilitates the coupling of the targeting vector and fluorescent dye at opposite sites to avoid undesired steric hindrance effects. The synthesis of the trifunctional chelate N3-Py-DOTAGA-(tBu)3 (7) involved a five-step synthetic route, followed by conjugation to the linear peptidyl-resin 8 through solid-phase synthesis. After deprotection and cyclization, the near-infrared fluorescent dye sulfo-Cy.5 was introduced using copper free click chemistry, resulting in eTFC-01. Subsequently, eTFC-01 was labeled with [111In]InCl3. In vitro assessments of eTFC-01 binding, uptake, and internalization were conducted in SSTR2-transfected U2OS cells. Ex-vivo biodistribution and fluorescence imaging were performed in H69-tumor bearing mice. Results eTFC-01 demonstrated a two-fold higher IC50 value for SSTR2 compared to the gold standard DOTA-TATE. Labeling of eTFC-01 with [111In]InCl3 gave a high radiochemical yield and purity. The uptake of [111In]In-eTFC-01 in U2OS.SSTR2 cells was two-fold lower than the uptake of [111In]In-DOTA-TATE, consistent with the binding affinity. Tumor uptake in H69-xenografted mice was lower for [111In]In-eTFC-01 at all-time points compared to [111In]In-DOTA-TATE. Prolonged blood circulation led to increased accumulation of [111In]In-eTFC-01 in highly vascularized tissues, such as lungs, skin, and heart. Fluorescence measurements in different organs correlated with the radioactive signal distribution. Conclusion The successful synthesis and coupling of the trifunctional chelate to the peptide and fluorescent dye support the potential of this synthetic approach to generate dual labeled tracers. While promising in vitro, the in vivo results obtained with [111In]In-eTFC-01 suggest the need for adjustments to enhance tracer distribution.